2021
DOI: 10.17509/jaset.v13i1.30783
|View full text |Cite
|
Sign up to set email alerts
|

The Moderating Role of Firm Size on the Association between Managerial Ability and Tax Avoidance

Abstract: Changes in taxation policies generate uncertainty for companies that can potentially encourage companies perform more aggressive tax planning. Aggressive tax planning can lead to tax avoidance. This study aims to investigate the effect of managerial ability, firm size, and the interaction of managerial ability with firm size on corporate tax avoidance practices. The study used quantitative method, with panel data linear regression model, random effects method, with a time period of 2009-2019. The results of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
2
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 43 publications
1
2
2
Order By: Relevance
“…The more profit in question can be obtained by avoiding taxes because the less the tax burden paid, the more profit the shareholders will get. The results of this study are in line with Raya and Saragih's (2021) research that managerial ability affects positively tax avoidance and states that more capable managers are found to be associated with greater tax avoidance because they have a better understanding of the business, environment, and opportunities that the company has so that these conditions allow managers to carry out more effective tax avoidance strategies. In addition, this study is also in line with research conducted by Koester et al (2017), who found consistent evidence regarding higher-ability managers engaging in more tax avoidance activities that reduce their company's cash tax payments.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…The more profit in question can be obtained by avoiding taxes because the less the tax burden paid, the more profit the shareholders will get. The results of this study are in line with Raya and Saragih's (2021) research that managerial ability affects positively tax avoidance and states that more capable managers are found to be associated with greater tax avoidance because they have a better understanding of the business, environment, and opportunities that the company has so that these conditions allow managers to carry out more effective tax avoidance strategies. In addition, this study is also in line with research conducted by Koester et al (2017), who found consistent evidence regarding higher-ability managers engaging in more tax avoidance activities that reduce their company's cash tax payments.…”
Section: Resultssupporting
confidence: 89%
“…Managerial ability is measured using DEA (Analysis Envelopment Data) where DEA and tax aggressiveness have a positive relationship. This is revealed in several studies, one of which is research conducted by Saragih et al (2021) which states that managers with higher abilities tend to be associated with greater tax avoidance because they have a deep understanding of business and opportunities.…”
Section: Managerial Skillsmentioning
confidence: 99%
“…So, managers with a better level of managerial ability will reduce tax avoidance activities. This study contradicts research conducted by (Akbari et al, 2018;Koester et al, 2017;Nurfauzi & Firmansyah, 2018;Saragih et al, 2021) which shows that there is a positive and significant relationship between managerial ability and tax avoidance.…”
Section: The Influence Of Managerial Ability On Tax Avoidancecontrasting
confidence: 92%
“…However, this study is different from the study (Akbari et al, 2018;Koester et al, 2017;Nurfauzi & Firmansyah, 2018;Saragih et al, 2021) which shows that managerial ability and tax avoidance are positively related. Managers with a higher level of managerial ability will engage in many tax avoidance activities that can reduce the company's cash tax payments.…”
Section: Introductioncontrasting
confidence: 90%
See 1 more Smart Citation